A test of the Bolton–Scheinkman–Xiong hypothesis of how speculation affects the vesting time of options granted to directors - Egger, Peter; Radulescu, Doina (Journal of Corporate Finance, 2014)
This paper investigates empirically the Bolton et al. (2006) hypothesis, according to which initial shareholders may provide incentives to managers to take actions that stimulate speculative bubbles. We test this hypothesis with data on up to 8544 directors and up to 1677 companies between 2004–2008. Using vesting time as a measure of the short-term performance weighting in CEO compensation and various alternative measures of the extent of speculation, the findings support the hypothesis: vesting time decreases with more intensive speculation. The results prove robust in various empirical model specifications.